Hubungan lama waktu pelingkaran jaring dan penarikan tali kerut terhadap jumlah produksi nelayan tangkap purse seine di Desa Kakenauwe Lasalimu Kabupaten Buton - Irfandi; Nurdiana A; Kamri, Syamsul; Lawelle, Sjamsu Alam (Jurnal Sosial Ekonomi Perikanan, 2024)
This study aims to determine the relationship between the time length for looping the net and pulling the corrugated rope on the production of purse seine fishermen in Kakenauwe village, Lasalimu district, Buton regency. The experiment was carried out from June to July 2021 in Kakenauwe Village, Lasalimu District, Buton Regency. The experiment used a random sampling technique with a total of 20 purse seine fishermen. The data collection process was carried out by means of observation, interviews, documentation, and literature studies. The data obtained were analyzed using the Cobb-Douglas formula and F test. The results of the analysis showed that the amount of production at the time length of setting and pulling the corrugated line in the purse seine fishing business from the calculation was strongly influenced by changes in the time length and the pulling of the corrugated line was 83.3 kg/minute. The second results showed that, based on the results of the f test the relationship between the length of time the net is encircled and the pulling of the crimped rope to the total production of purse seine fishermen simultaneously was significantly effect on the total production of purse seine fishermen because the calculated f value was more higher than the f table value (F table = 0.05 > 0.01)